An Analysis of Cohesion in Academic Discourse on Science Based on the Theory of Functional Grammar: (Analisis Kohesi Wacana Sains Berdasarkan Teori Nahu Fungsian) (Jurnal Bahasa, 2015)
This study aims to identify the form and strategy of cohesion in selected articles on science. The data for this study consists of 24 Malay articles which were published in the Sains Malaysiana journal in the year of 2012. These selected articles on science are taken from three disciplines of science, i.e., biology (10 articles), chemistry (8 articles) and physics (6 articles). The articles are analyzed based on the Wordsmith Tools 5 program to identify the form and frequency of cohesion in the sentences. This study applied the model of cohesion that was proposed by Halliday and Hasan (1976). According to this model, there are five major types of cohesion: reference, substitution, ellipsis, conjunction and lexical cohesion. Specifically, this study only concentrated on reference, conjunction and lexical cohesion. This study found that repetition of lexical item is the most frequently used. It is followed by reference and conjunction. As a form of academic writing, the articles on science are charcterized by objectivitity, logic and precision. The findings of this study may contribute to a better understanding of the types and strategies of cohesion in Malay scientific texts.Keywords: cohesion, academic discourse on science, WordSmith Tools 5, scientific text